Extrafacial Lentigo Maligna: A Clinical And Dermoscopic Analysis According to Localization - Gabriel Salerni; Emilia Cohen-Sabban; Horacio Cabo (Mattioli1885, 2022)
Introduction: Whether extrafacial lentigo maligna (EFLM) differs clinically and/or dermoscopically according to location has not been analyzed in depth. Objectives: To evaluate clinical and dermoscopic characteristics regarding different localization in a series of EFLM. Methods: We conducted a retrospective analysis of clinical and dermoscopic characteristics of 69 histologically proven EFLM retrieved from the database of two private institutions. Results: Of the 69 EFLM included in the study, 25 (36.2%) were located in posterior trunk (PT), 16 (23.2%) in anterior trunk (AT), 15 (21%) in upper extremities (UE), and 13 (18.8%) in lower extremities (LE). Mean diameter among localization were as follows: 14.3 mm in PT, 11.8 mm in AT, 14 mm in UE, and 10 mm in LE (p 0.44). The most frequent dermoscopic criteria were angulated lines and tan structureless areas (70%), followed by atypical pigment network (60%), both with similar distribution among groups. Angulated lines pattern was the most frequent global pattern, observed in 55% of cases. Tan structureless/granularity pattern and patchy peripheral pigmented islands pattern were seen in 15.6% and 11.6% cases, respectively. No statistically significant differences were observed in the distribution of global dermoscopic pattern in the different localizations. Conclusions: From the clinical point of view, EFLM did not differ in terms of patient's age and diameter regarding localization. Upon dermoscopy, we found no significant differences in the overall dermoscopic pattern in the different localizations.